PERENCANAAN DANA DESA DALAM MENGENTASKAN KEMISKINAN DI DESA MEKARSARI KECAMATAN CIKAJANG KABUPATEN GARUT - Kurniawan, Fitra; Myrna, Rita (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
ABSTRACT This research is motivated by the high and increasing poverty rate in Mekarsari Village. Based on the Permendes PDTT number 7 of 2021 concerning the priority use of village funds in 2022, it states that village funds are prioritized for the achievement of village SDGs, one of which is poverty reduction. Mekarsari village has not been able to reduce the poverty rate of the community, so optimization is needed in Village Fund planning. The purpose of this study was to describe how the Village Fund planning in poverty alleviation in Mekarsari Village, Cikajang District, Garut Regency, using the management organizational planning theory of Ernie Tisnawati Sule and Kurniawan Saefullah. This study uses descriptive qualitative research methods with primary data obtained through observation and interviews, as well as secondary data through the study of documents and literature. Data analysis in this study was conducted through data reduction, presentation of data, as well as the affirmation of conclusions and verification. The results obtained from this study stated that the Village Fund planning in Mekarsari Village is still not effective, especially in the factual, flexible, commitment, and comprehensive dimensions so it needs to be optimized and improved again. Keywords: Village Fund; Planning; Poverty; Village